THE VOCABULARY MASTERY OF THE EIGHTH YEAR STUDENTS OF SMP BHAKTI MALANG USING ANAGRAM GAMES - Endang Setyowati; Lu’lu’il Maknuun (UIBU, 2020)
The aim of the research is to know the English vocabulary mastery of the students of SMP Bhakti Malang taught by using anagram games, therefore this research used classroom action research (CAR). This research uses individual CAR that focuses only in one classroom. In addition, the researcher acts as the practitioner that conducts the teaching and learning activity by using Anagram game and as an observer that monitored the teacher’s teaching and also the process of teaching. The subjects of the study are eighth grades of SMP Bhakti Malang in second semester at academic year 2019-2020 class 8A is chosen because their English achievement has not provided satisfactory result. The result shows that there was an improvement of the students’ mean score from preliminary test 56.66 (under the minimum passing grade) increase to 74.25 (pass the minimum passing grade) in test 1 and up to 84.44 in test 2. The standard deviation which decreased from 12.50 in test 1 to 8.34 in test 2 indicates that the students’ score close around the mean score which have passed the minimum passing grade.The success of the Anagram strategy in improving the students’ vocabulary is also supported by the creativity of the teacher in designing appropriate media and material, designing the lesson plan, varying classroom activities and building the cooperation among the students.